The effect of feed-in-tariff supporting schemes on the viability of a district heating and cooling production system - Jiménez-Navarro, Juan-Pablo; Cejudo-López, José Manuel; Connolly, David (My University, 2017)
Combined cooling, heat and power systems represent an efficient alternative to supply heating and cooling demand compared to conventional boilers and air conditioner systems. However, considering the high level of upfront investment and the relatively long lifetimes, it is important to provide some form of long-term certainty to reduce the risk of deployment of these systems. To overcome this uncertainty, this paper describes a method to calculate an appropriate feed-in-tariff scheme to support investors and public authorities to foster the penetration of this technology in areas with high energy demands. It is subsequently tested in a scientific and technology park located in the south of Spain where different energy prices are studied. The results indicate that a feed-in-tariff is required to support the development of combined heating, cooling, and power systems, which not only improves the economic performance of the system, but also increases the utilisation of more efficient generation technologies such as combined cooling, heat and power systems.
Keywords: Aire acondicionado; Combined cooling, heat and power; Combined heat and power; Energy policy Optimisation; Feasibility; Feed-in-tariff